Development of Technology for the Production of Compositive Materials for the Manufacture of Automobile Spare Parts on the Basis of Secondary Polymer Raw Materials (The Peerian Journal, 2022)
The scientific significance of the results of this work is determined by the creation of a scientific basis for the production of modifiers and composite materials with previously known properties. The effect of the amount of various modified additives on the physical and mechanical properties of the obtained composite was studied.